Homeopathic Rhus toxicodendron Induces Cell Adhesions in the Mouse Pre-osteoblast Cell Line MC3T3-e1 - Oh, Young Soo; Chae, Soo Chul; Kim, Hwan; Yang, Hun Ji; Lee, Kyung Jin; Yeo, Myeong Gu (Homeopathy, 2021)
Background Rhus toxicodendron (R. tox) has been used as a homeopathic remedy for the treatment of inflammatory conditions. Previously, we reported that R. tox modulated inflammation in the mouse chondrocyte and pre-osteoblastic MC3T3-e1 cell line. During the inflammatory process, cells adhere to the extracellular matrix (ECM) and then migrate to the inflammation site. We examine here the process of cell adhesion in MC3T3-e1 cells after their stimulation with homeopathic R. tox.Methods For the cell–substrate adhesion assay, the cultured MC3T3-e1 cells were trypsinized, starved for 1 h in serum-free media, and plated onto culture plates coated with fibronectin (FN), 30c R. tox or gelatin, respectively. The cells were allowed to adhere for 20 min incubation and unattached cells were washed out. Adherent cells were measured using the water-soluble tetrazolium salt-8 assay. The intracellular signals after stimulation of R. tox were examined by analyzing the tyrosine phosphorylation of focal adhesion kinase (FAK), Src kinase, and Paxillin using immunoblot assay. Formation of focal adhesion (FA, an integrin-containing multi-protein structure that forms between intracellular actin bundles and the ECM) was analyzed by immunocytochemistry using NIH ImageJ software.Results Cell adhesion increased after stimulation with R. tox (FN, 20.50%; R. tox, 44.80%; and gelatin, 17.11% vs. uncoated cells [control]). Tyrosine phosphorylation of FAK, Paxillin, and Src increased compared with that of gelatin when stimulated with R. tox. Additionally, R. tox-stimulated cells formed many FAs (number of FAs per cell, 35.82 ± 7.68) compared with gelatin-stimulated cells (number of FAs per cell, 19.80 ± 7.18) and exhibited extensive formation of actin stress fibers anchored by FAs formed at the cell periphery.Conclusion Homeopathic R. tox promotes the formation of cell adhesions in vitro.
Keywords: Rhus toxicodendron; cell adhesion; fibronectin; focal adhesion